Study on Multi-RAT Coordination in 5G - Yunlu Liu; Guang Yang; Ning Yang; Zhuo Chen; Nan Hu; Nan Li; Fang Xie; KDA Boubacar; Guangyi Liu (Dianxin kexue)
It is common to operate more than one RAT of operators，who are confronted with complicated cooperation among multiple RATs，and relative low multi-RAT cooperating efficiency. How to facilitate efficient multi-RAT coordination to improve cooperation efficiency and user experience has become an important research topic with broad application prospects. The research supplements each other with 5G network architecture design. On the basis of analyzing background and research status，key technologies were addressed. A paradigm of logical architecture was given and discussed from multi-RAT point of view. And further solutions of user/core agnostic multi-RAT unified access and seamless mobility were given to shorten cooperation path，reduce complexity of cooperation，and improve cooperating efficiency as well as user experience.